Peningkatan Kemandirian Activity of Daily Living Siswa Disabilitas Fisik berbasis Aplikasi Dikta Care dan Alat Teknologi Bantu - Mundakir; Choliq, Idham; Hakim, Lukman (Universitas Muhammadiyah Surakarta, 2023)
Mitra SDLB YPAC Surabaya stated that there are still many students with physical disabilities who cannot perform self-care such as wearing their own clothes, eating, drinking, bathing, toileting, decorating and mobilizing. A total of 4 students were partially assisted and 12 students were fully assisted in performing activities of daily living (ADL). Partners do not yet have materials for self-care. This is due to the unavailability of effective learning media that supports the improvement of ADL independently at SDLB YPAC Surabaya. This is due to the unavailability of effective learning media that supports the improvement of ADL independently at SDLB YPAC Surabaya. In addition, there are no special assistive devices that can support the self-care of children with disabilities independently. The purpose of this service is to increase the independence of students with disabilities in doing ADL. The implementation method consists of 4 stages, namely the preparation stage, implementation stage, monitoring and evaluation stage, and program sustainability. This service program has achieved results that teachers' knowledge about self-care for children with disabilities increased with a good category of 14 (87.5%), a medium category of 2 (12.55), and a low category of 0 (0%). Based on the evaluation of the level of independence, there is a change in the level of independence. The assessment before the action of the partially assisted category was 4 students, but after being given the innovation tool increased to 6 students, and students who were fully assisted initially were 12 reduced to 10 students. Even so, the full level of independence has not yet been achieved. So that it takes a long time to train students with disabilities by using late-made cutlery innovations.